(untitled) (Bangladesh Journal of Anatomy, 2013)
Context: Malignant neoplasms of cervix uteri is a major medical condition with aging population. Detailed anatomical knowledge about cervix uteri is important for obstetracian, pathologist and physician for proper diagnosis and management of cervical diseases. Study design: Cross sectional, analytical type of study. Place and period of study: Department of Anatomy, Sylhet M A G Osmani Medical College, Sylhet, from July 2006 to June 2007. Materials: Present study was performed on 50 autopsied human uterus, age ranging from 1 to 65 years. The samples were collected from unclaimed dead bodies that were under examination in the morgue of the Department of Forensic Medicine of Sylhet M A G Osmani Medical College, Sylhet. Methods: The samples were divided into four age groups. Group A (1-12 years), Group B (13-24 years), Group C (25-46 years) and Group D (46-65 years). All the samples were studied morphologically. Results: Statistically significant positive correlation was found between age and length, breadth and thickness of cervix Conclusion: There were changes in the morphology of cervix in relation to age. DOI: http://dx.doi.org/10.3329/bja.v10i2.17323 Bangladesh Journal of Anatomy, July 2012, Vol. 10 No. 2 pp 80-83